Cigarette filter butts-derived activated carbon with free binder electrode design for solid-state supercapacitor application: From hazardous waste to solid-state supercapacitor - Hamzah, Yanuar; Taer, Erman; Apriwandi, Apriwandi; Supian, Faridah Lisa; Mozaffari, Niloofar; Mozaffari, Nastaran (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2023)
The aim of this research is to formulate activated carbon monolith from hazardous waste of cigarette filter butts (CFB) for electrode material monolith design in solid-state supercapacitor application. Potassium hydroxide (KOH) was selected for activation. The ratio of CFB to KOH varied in terms of weight between 1:2 and 1:4, thereby obtaining activated cigarette filter carbon (ACFC). The carbon that has been obtained is designed to be solidly in the form of an additive-free monolith. Monolith-activated carbon is physically characterized to examine thermal decomposition profiles (pre-carbonized), structure, composition, morphology, surface area adsorption, and electrochemical measurements. The optimum precursor was marked with high wettability with self-O-doped of 5.44%.in carbon content of 94.56%. Activated carbon electrodes prepared from ACFCs showed an optimum specific capacitance of 87.17 F g-1, which is a more ecologically responsible method of producing supercapacitors.